Design of variable-rate liquid fertilization control system and its stability analysis - Zhang, Jicheng; Hou, Shouyin; Wang, Runtao; Ji, Wenyi; Zheng, Ping; Wei, Shi (International Journal of Agricultural and Biological Engineering, 2018)
Variable-rate technology (VRT) has been paid more attentions by farmers in an attempt to match inputs to local growing conditions efficiently. Farmers in every country are highly encouraged to adopt this practice rather than uniform-rate application (URA). However, the standard methods and design used to quantify application accuracy for VRT remain lacking. Therefore, a variable-rate liquid fertilization control system was designed to meet accurate fertilization demand. The designed control system could enable the real-time proportion and mixture of three kinds of liquid fertilizers, namely, N, P and K, in accordance with decision support subsystem. The task controller reads related information and sends such data to the control system, which is responsible for fertilization operation. The controller could realize liquid fertilizer adjusting through the electromagnetic flow control valves. A high-precision flow meter could measure the fertilization amount, which is sent as feedback to the controller to form a closed-loop control system based on the improved proportional-integral-derivative (PID) control algorithm that could enhance the stability and accuracy of precision variable-rate liquid fertilization control systems. Comparisons between the actual and planned application rates indicated good performance for both static and field experimental trials. Mathematical models and transfer functions for some functional modules were then constructed by classical theories to derive a system characteristic equation. To verify the static and dynamic performances, the control system was simulated using the Simulink module on Matlab. Results showed that the variable-rate fertilization was in accordance with the planned data and that the signal trace effect was good. The error was less than 5% for fertilization amount and fertilizer proportion, respectively, and the control response time was 6 s.Keywords: fertilization control system, variable-rate technology, precision fertilization, closed-loop control system, improved PID control algorithm, SimulinkDOI: 10.25165/j.ijabe.20181101.2583Citation: Zhang J C, Hou S Y, Wang R T, Ji W Y, Zheng P, Wei S. Design of variable-rate liquid fertilization control system and its stability analysis. Int J Agric & Biol Eng, 2018; 11(1): 109–114.